Case Report: Uniportal Video Assisted Thoracoscopic Excision of a Giant Thymic Cyst Mimicking a Pericardial Cyst - Alzafer, Suha; Okur, Erdal; Halezeroğlu, Semih (Acıbadem Mehmet Ali Aydınlar Üniversitesi, 2015)
ABSTRACT Most of the mediastinal cysts are benign but still needs surgical excision for a definitive diagnosis and to prevent compressive symptoms. Radiological examination itself may sometimes have limited diagnostic value. A pericardial cyst is always a benign lesion and does not need an excision unless it reaches to an extreme size while a thymic cyst should be excised when diagnosed since it may rarely show malignant degeneration. Here we present an extreme sized thymic cyst radiologically mimicking a pericardial cyst.